Inheritance Disputes Due to Errors and Omissions in the Civil Registry: Legal Implications of the Lack of Documented Identity and Family Ties - Martín, Pinchi Bartra; César, Velazco Lévano, Nilton; Daniel, Coral Pérez Victor (Journal of Ecohumanism, 2024)
This research analyzed inheritance conflicts arising from fraudulent errors and omissions in Peru, to determine the legal implications of the lack of identity and documented family ties, due to the lack of transparent access to information on ancestors and descendants recognized by the State. The study was developed under a qualitative approach with grounded theory design, using documentary analysis to examine judicial files. The analysis of ten files revealed that deficiencies in the documentation of identity and family ties facilitated the deliberate exclusion of forced heirs and the manipulation of inheritance processes, especially when there were errors in the civil registries or late registrations. The investigation concluded that it was urgent to modernize the Civil Registry System through an interoperable registry system with effective verification mechanisms to guarantee the equitable transmission of inheritance rights and protect the legitimate interests of heirs.